Determining the required level of care for patients with acute bacterial meningitis: case reports and literature review - G. Makarevičius; N. Giedraitienė; A. Klimašauskienė (Neurologijos seminarai)
Bacterial meningitis remains a disease associated with high mortality. Thus, in some hospitals admission of most patients presenting with bacterial meningitis to the intensive care unit (ICU) was a standard procedure. However, ICUs require advanced technologies and highly specialized personnel. Since both economic and human resources are scarce, countries are attempting to develop the most accurate ICU admission criteria that can minimize over- and undertriage. The guidelines designed so far mainly suggest admitting patients to ICU based on their neurological status. However, since neurological condition is not the only factor contributing to the outcomes of bacterial meningitis, over- and undertriage cannot always be avoided. In this article, we present two cases of bacterial meningitis: an elderly man who was denied ICU care since his consciousness was only mildly altered, and a woman who was admitted to ICU because she was diagnosed with meningococcus meningitis. We will also review some literature regarding prognostic factors for bacterial meningitis in an attempt to distinguish valuable criteria for ICU admission.